2007
DOI: 10.1152/japplphysiol.00691.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Importance of pH regulation and lactate/H+transport capacity for work production during supramaximal exercise in humans

Abstract: We examine the influence of the cytosolic and membrane-bound contents of carbonic anhydrase (CA; CAII, CAIII, CAIV, and CAXIV) and the muscle content of proteins involved in lactate and proton transport [monocarboxylate transporter (MCT) 1, MCT4, and Na(+)/H(+) exchanger 1 (NHE1)] on work capacity during supramaximal exercise. Eight healthy, sedentary subjects performed exercises at 120% of the work rate corresponding to maximal oxygen uptake (W(max)) until exhaustion in placebo (Con) and metabolic alkalosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 49 publications
6
101
2
2
Order By: Relevance
“…Similarly independent of CA inhibition, ACTZ improved symptoms of vacuolar myopathy upon experimental K ϩ depletion, not only by stimulating BK channels but also by reducing lactate efflux (39). Normally, lactate efflux from the muscle decreases upon inhibition of extracellular CA, as shown in rats (42) and in exercising humans (17,23), implying the high importance of muscular CA isoenzymes in lactate (and pH) regulation for work capacity in exercising humans (21). Therefore, it remains unclear, whether adverse effects of ACTZ on skeletal muscles in healthy subjects, such as muscle fatigue and decreased exercise tolerance, are related to CA inhibition and should thus occur on treatment with MTZ as well, or whether they are a matter of additional specific effects of ACTZ on lactate efflux or BK channels.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly independent of CA inhibition, ACTZ improved symptoms of vacuolar myopathy upon experimental K ϩ depletion, not only by stimulating BK channels but also by reducing lactate efflux (39). Normally, lactate efflux from the muscle decreases upon inhibition of extracellular CA, as shown in rats (42) and in exercising humans (17,23), implying the high importance of muscular CA isoenzymes in lactate (and pH) regulation for work capacity in exercising humans (21). Therefore, it remains unclear, whether adverse effects of ACTZ on skeletal muscles in healthy subjects, such as muscle fatigue and decreased exercise tolerance, are related to CA inhibition and should thus occur on treatment with MTZ as well, or whether they are a matter of additional specific effects of ACTZ on lactate efflux or BK channels.…”
Section: Discussionmentioning
confidence: 92%
“…Among the variety of mechanisms to maintain pHi in response to changes in pHe, MCTs have been shown to play key roles particularly at low pHe values (26)(27)(28). Because we showed that MCT4 expression was reduced at pH 6.5, we examined the expression of MCT1, a more ubiquitous MCT isoform supporting transport of H þ /lactate and ketone bodies.…”
Section: Glycolysis Inhibition Only Partly Mimics Acidosistriggered Imentioning
confidence: 99%
“…Situação essa também verificada em ratos (21,22) . Segundo Messonnier et al (23) , um mecanismo celular de tamponamento representaria a primeira linha de defesa contra a acidose e o acúmulo de lactato, podendo melhorar sua capacidade de trabalho. Esse mecanismo seria baseado em proteínas transportadoras de monocarboxilatos (MCT1 e MCT4) presentes na membrana do sarcolema e da mitocôndria, que elevariam o transporte intracelular dos prótons e lactato para o interstício durante o exercício.…”
Section: Discussionunclassified
“…Sob essas condições, paralelamente à elevação na produção de lactato, a taxa de liberação de prótons pela glicólise e hidrólise de ATP torna-se maior, o que pode exceder a capacidade tamponadora da célula e provo-car acidose muscular. Essa acidose metabólica pode desempenhar um papel determinante na intolerância ao exercício, desencadeando um declínio na força em função do prejuízo no processo excitação-contração, depressão da força ativada pelo Ca 2+ e potencializando a fadiga muscular (23) . Por outro lado, Robergs et al (29) sugerem que a elevação do lactato é mais uma consequência do que causa da acidose metabólica.…”
Section: Discussionunclassified